2020
DOI: 10.1007/s11144-020-01781-0
|View full text |Cite
|
Sign up to set email alerts
|

The isomerization of S-carvone over the natural clinoptilolite as the catalyst: the influence of reaction time, temperature and catalyst content

Abstract: This work describes the isomerization of S-carvone using a natural zeolite-clinoptilolite as the catalyst. The isomerization of S-carvone was carried out at the catalyst content in the reaction mixture from 5 to 15 wt%, in a temperature range of 190-210 °C and for the reaction time from 60 to 300 min. The main product of the isomerization of S-carvone was aromatic alcohol with many practical applicationscarvacrol. The use of the most favorable reaction conditions (the reaction time of 3 h, the temperature of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Reports on its use in catalytic reactions such as cracking, isomerization, alkylation, and methanol to olefin conversion remain restricted despite its low cost and wide availability. [12,14,22,[34][35][36][37][38][39] This study investigates the acetalization process of benzaldehyde with butanediol-1,3 employing Brønsted acid catalysis while also examining the impact of acidic modification on a natural zeolite sample and its catalytic activity. The research delves into the stability of aluminum and Brønsted acid sites within the tetrahedral framework concerning temperature, employing comprehensive analysis methods such as nitrogen adsorption-desorption tests, ammonia temperature-programmed desorption (TPD), and 27 Al magic-angle spinning (MAS) nuclear magnetic resonance (NMR) spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports on its use in catalytic reactions such as cracking, isomerization, alkylation, and methanol to olefin conversion remain restricted despite its low cost and wide availability. [12,14,22,[34][35][36][37][38][39] This study investigates the acetalization process of benzaldehyde with butanediol-1,3 employing Brønsted acid catalysis while also examining the impact of acidic modification on a natural zeolite sample and its catalytic activity. The research delves into the stability of aluminum and Brønsted acid sites within the tetrahedral framework concerning temperature, employing comprehensive analysis methods such as nitrogen adsorption-desorption tests, ammonia temperature-programmed desorption (TPD), and 27 Al magic-angle spinning (MAS) nuclear magnetic resonance (NMR) spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its porous nature and potential as a catalyst via ion exchange or acid treatment, [2,12,14,33] its application in catalysis is limited due to insufficient activity or stability. Reports on its use in catalytic reactions such as cracking, isomerization, alkylation, and methanol to olefin conversion remain restricted despite its low cost and wide availability [12,14,22,34–39] …”
Section: Introductionmentioning
confidence: 99%
“…It was shown that this process was most favorably performed at 210 • C, with the catalyst content of 15 wt% and for 3 h. Under these conditions, the yield of carvacrol amounted to 90 mol%. The therapeutic properties of carvacrol, such as, its analgesic, antioxidant, antibacterial, antiparasitic, and antifungal properties, make it suitable for use in medicine [27].…”
Section: Introductionmentioning
confidence: 99%
“…Carvacrol is contained in essential oil of oregano, thyme or savory. A large scale of carvacrol biologic effects (antibacterial, insecticidal, antifungal, analgetic, antioxidant or antiparazitic) was reported [1,2]. Moreover, carvacrol can be oxidized to obtain thymoquinone-a substance with possible anticancer, antioxidant and cholesterol lowering effects.…”
Section: Introductionmentioning
confidence: 99%
“…Yield of carvacrol > 96% was obtained (160 • C, toluene, 3 h [15]) in the case of montmorillonite. A natural zeolite-clinoptilolite was also catalytically active in carvone isomerization-yield of carvacrol > 90% was obtained in solvent-free synthesis (210 • C, 3 h [1]). Rare mentions of specific catalysts, e.g., complex of NHC ligand and palladium or Pt(IV) complex, can be also found [11,16].…”
Section: Introductionmentioning
confidence: 99%